Public Theology and the economy in a globalizing world - Bedford-Strohm, H (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
This paper was read at the Theological Day of the Faculty of Theology, Stellenbosch University on 25 January 2010. Speaking on “Public Theology and the economy in a globalizing world” in 30 minutes is a real challenge. The themes of Public Theology, of basic assumptions of economics and of what we mean by the word “globalization” would be each one a lecture of its own. And yet the connection of the three is exactly what needs to be discussed. The challenge of a globalizing world which has destructive effects on the natural environments and which still tolerates the poverty caused death of thousands of human beings every day is clearly on the table. I will leave describing these challenges of globalizations more closely to others today and focus on the theological grounding. After a reflection on the relationship of theology and economics in the reformation traditions, I will describe the place of a public theological model of economic ethics in the context of several other models. I will explain what it entails by distinguishing four dimensions of ethical reflection and conclude with exploring the task of the church in a globalizing world.